Conscientiousness in Teams Completing Creative Tasks: Does it Predict?. (11th June 2020) - Taggar, Simon
Abstract: The relationship between conscientiousness and creativity remains equivocal. This is surprising because conscientiousness is a good predictor of job performance across most criteria and occupations. In this longitudinal study, I found support for the achievement striving and the dependability aspects of conscientiousness affecting team member creativity in different ways. Specifically, the achievement striving aspect of conscientiousness positively predicts creative self‐efficacy, but the dependability aspect negatively predicts creative self‐efficacy. Conversely, dependability positively predicts teamwork self‐efficacy, while achievement striving is unrelated to teamwork self‐efficacy. Creative self‐efficacy partially mediates between achievement striving and team member creativity. Both creative self‐efficacy and teamwork self‐efficacy mediate between dependability and team member creativity.